Research and clinical skills in the training of medical students - Pablo Andres Vergara Barra; Patricia Rubi González; Ximena Macaya Sandoval (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2019)
This work contains the results of a bibliographic review carried out with the objective of exposing the importance of the development of research and clinical skills in the process of training of medical students. It is found that promoting research in students allows, among other things, to open the doors of knowledge to the development of new technologies and procedures in different medical specialties. It can be concluded that enhancing the interest of students in research validates the scientific method as an articulating cord between training content and clinical skills, along with benefiting the work with their patients, promoting the implementation of better health responses.